Pseudomonas Exotoxin-Based Immunotoxins: Over Three Decades of Efforts on Targeting Cancer Cells With the Toxin - Havaei, Seyed Mehdi; Aucoin, Marc G.; Jahanian-Najafabadi, Ali (Frontiers in Oncology, 2021)
Cancer is one of the prominent causes of death worldwide. Despite the existence of various modalities for cancer treatment, many types of cancer remain uncured or develop resistance to therapeutic strategies. Furthermore, almost all chemotherapeutics cause a range of side effects because they affect normal cells in addition to malignant cells. Therefore, the development of novel therapeutic agents that are targeted specifically toward cancer cells is indispensable. Immunotoxins (ITs) are a class of tumor cell-targeted fusion proteins consisting of both a targeting moiety and a toxic moiety. The targeting moiety is usually an antibody/antibody fragment or a ligand of the immune system that can bind an antigen or receptor that is only expressed or overexpressed by cancer cells but not normal cells. The toxic moiety is usually a protein toxin (or derivative) of animal, plant, insect, or bacterial origin. To date, three ITs have gained Food and Drug Administration (FDA) approval for human use, including denileukin diftitox (FDA approval: 1999), tagraxofusp (FDA approval: 2018), and moxetumomab pasudotox (FDA approval: 2018). All of these ITs take advantage of bacterial protein toxins. The toxic moiety of the first two ITs is a truncated form of diphtheria toxin, and the third is a derivative of Pseudomonas exotoxin (PE). There is a growing list of ITs using PE, or its derivatives, being evaluated preclinically or clinically. Here, we will review these ITs to highlight the advances in PE-based anticancer strategies, as well as review the targeting moieties that are used to reduce the non-specific destruction of non-cancerous cells. Although we tried to be as comprehensive as possible, we have limited our review to those ITs that have proceeded to clinical trials and are still under active clinical evaluation.